2021
DOI: 10.3390/plants10102045
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin-LR, a Cyanobacterial Toxin, Induces DNA Strand Breaks Correlated with Changes in Specific Nuclease and Protease Activities in White Mustard (Sinapis alba) Seedlings

Abstract: There is increasing evidence for the induction of programmed cell death (PCD) in vascular plants by the cyanobacterial toxin microcystin-LR (MC-LR). Our aim was to detect the occurrence of PCD-related DNA strand breaks and their possible connections to specific nuclease and protease activities. DNA breaks were studied by the deoxynucleotidyl transferase mediated dUTP nick end labeling (TUNEL) method in the photoperiodically grown dicot model of white mustard (Sinapis alba). In-gel nuclease and protease activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This study suggested that microcystin affected photosynthesis with a reversible, short-term effect at a single application of low concentration and with an irreversible, long-term effect at high concentration with a single application or when multiple applications at low concentrations are used [74]. In most cases, the alterations may be directly related to the specific biochemical effects of cyanotoxins as inhibition of protein phosphatases 1 and 2A and of protein synthesis [70,75]. Cyanotoxins cause spindle abnormalities and mitotic spindle disruptions in several plant species leading to distorted organs and growth inhibition [69][70][71]76].…”
Section: Toxinsmentioning
confidence: 92%
See 3 more Smart Citations
“…This study suggested that microcystin affected photosynthesis with a reversible, short-term effect at a single application of low concentration and with an irreversible, long-term effect at high concentration with a single application or when multiple applications at low concentrations are used [74]. In most cases, the alterations may be directly related to the specific biochemical effects of cyanotoxins as inhibition of protein phosphatases 1 and 2A and of protein synthesis [70,75]. Cyanotoxins cause spindle abnormalities and mitotic spindle disruptions in several plant species leading to distorted organs and growth inhibition [69][70][71]76].…”
Section: Toxinsmentioning
confidence: 92%
“…Cyanotoxins cause spindle abnormalities and mitotic spindle disruptions in several plant species leading to distorted organs and growth inhibition [69][70][71]76]. These alterations were triggered by a change in the phosphorylation status of proteins (e.g., microtubule associated proteins) that regulates spindle assembly and leads to abnormal segregation of sister chromatids in mitosis [70,76]. Subcellular alterations induced by cyanotoxins, as shown above, generally anticipate the plant cell death [69].…”
Section: Toxinsmentioning
confidence: 95%
See 2 more Smart Citations